Analysis of factors influencing the stated preference of academic employees towards telecommuting in IIUM campus, Gombak - Ismail, Farah Diyanah; Kadar Hamsa, Abdul Azeez; Ibrahim, Mansor (Malaysian Institute of Planners, 2012)
Telecommuting acts as one of the Transportation Demand Management (TDM) measures that aimed to reduce peak hour traffic congestion by allowing commuters to work from home or a nearby telecommuting centre on certain days of the week. The increasing private vehicle usage by IIUM community (staffs and students) is posing a strain on the ability of the existing road and the related infrastructure on-campus. The purpose of this paper is to investigate factors influencing the stated preference of the academic staffs of IIUM towards various aspects of telecommuting. About 100 respondents had participated in this study through a self-administered questionnaire survey. Four research hypotheses highlighting the relationship between the preference to telecommute and commute distance, commute time, marital status having children as well as amount of time spent on research were formulated. Among the hypotheses, only the hypothesis highlighting the preference to telecommute and married female staff with children was tested statistically significant at 95% confidence interval. On the preference to telecommute, about 68% of the respondents expressed willingness to telecommute, even though, the University does not have an official policy on telecommuting arrangement. Some of the recommendations to increase the penetration of telecommuting in IIUM are: establishing telecommuting arrangement; promoting awareness of telecommuting; implementing telecommuting pilot project and conducting further study on various other aspects of telecommuting.